Ureteral Clipping Simplifies Hand-Assisted Laparoscopic Donor Nephrectomy - Brown, James A. (Society of Laparoendoscopic Surgeons, 2010)
OBJECTIVES: We describe a technique of doubly clipping the distal ureter during hand-assisted laparoscopic donor nephrectomy (HALDN) to prevent urine accumulation, thereby simplifying renal hilar division and potentially decreasing the graft warm ischemic time. METHODS: A technique of placing polymer-locking clips across the distal ureter prior to division was developed to prevent urine accumulation and the need for suctioning during critical hilar vessel division. RESULTS: We found that ureteral clipping and the elimination of urine accumulation simplified renal hilar division. Retrospective assessment of a series of 27 sequential HALDNs (15 without and 12 with clipping) demonstrated similar estimated blood loss, total operative and warm ischemic times (P=0.13 to 0.18). No adverse impact on graft viability or recipient outcome was observed. CONCLUSION: Distal ureter clipping to prevent urine accumulation around the renal hilum during HALDN is safe and helpful.